2005
DOI: 10.1021/ic050219k
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Carbonyl-Containing Intermediate in the 308-nm Photolysis of trans-RhCl(CO)(PMe3)2

Abstract: Time-resolved infrared absorption spectroscopy is used to monitor the events during the first approximately 100 mus following 308-nm photolysis of trans-RhCl(CO)(PMe3)2 (I) in a C6D6 or Decalin solution. Upon photolysis, the intensity of the carbonyl stretching absorption of I decreases and a new C-O stretching absorption (A) appears at 2006 cm(-1) in C6D6 (2013 cm(-1) in Decalin). Within approximately 100 mus, A disappears concurrently with partial regeneration of I and oxidative addition of a solvent C-D (C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…[16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2). [16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2).…”
Section: Spectroscopic Investigations and Reaction Mechanismsupporting
confidence: 66%
See 3 more Smart Citations
“…[16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2). [16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2).…”
Section: Spectroscopic Investigations and Reaction Mechanismsupporting
confidence: 66%
“…After 10 min, two new bands appear simultaneously at ñ = 1986 and 2065 cm À1 , which can be assigned to the n(Rh III ÀCO) and n(Rh III ÀH) modes, respectively. [16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2). Alternatively, these bands might stem from two different intermediate Rh complexes that contain either CO or H as the ligand (vide infra).…”
Section: Spectroscopic Investigations and Reaction Mechanismsupporting
confidence: 66%
See 2 more Smart Citations